Evaluation of the efficacy and safety of flumazenil in the treatment of portal systemic encephalopathy: a double blind, randomised, placebo controlled multicentre study. Issue 2 (August 1996) - Gyr, K; Meier, R; Häussler, J; Boulétreau, P; Fleig, W E; Gatta, A; Holstege, A; Pomier-Layrargues, G; Schalm, S W; Groeneweg, M; Scollo-Lavizzari, G; Ventura, E; et al.
Abstract : BACKGROUND: Portal systemic encephalopathy (PSE) is a complex neuropsychiatric syndrome associated with hepatic failure. Small scale studies have shown the benzodiazepine receptor antagonist flumazenil to be effective in ameliorating PSE. AIMS: To determine the efficacy of flumazenil in patients with non-comatous mild to moderate PSE (stages I to III) due to severe chronic liver disease. PATIENTS: 49 male and female adults without symptoms of severe bleeding and sepsis and who screened negative for benzodiazepine in both blood and urine, were included in the study. METHODS: Patients were randomised to receive either three sequential bolus injections of flumazenil (0.4, 0.8, and 1 mg) or placebo at one minute intervals, followed by intravenous infusions of either flumazenil (1 mg/h) or placebo for three hours. Clinical PSE grading and vital signs were assessed hourly during baseline and post-treatment periods and half hourly during treatment. The main outcome measures were improvement in group average PSE score and reduction of two points in individual PSE score (clinically relevant improvement). RESULTS: The mean average improvement in the PSE score in the subjects treated with flumazenil was not statistically significantly different from placebo. However, for patients showing clinically relevant improvement, the difference between flumazenil and placebo was statistically significant (seven of 28 v none of 21; p = 0.015). Flumazenil was well tolerated. CONCLUSIONS: A subgroup of patients with PSE resulting from chronic liver disease may benefit from the administration of flumazenil.